ANALISIS KINERJA KEUANGAN KOPERASI PEGAWAI REPUBLIK INDONESIA PLN AREA IV, TAMAN, SIDOARJO - Tania Amalia Khoirunnisa; Muchammad Saifuddin (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
This study aims to determine the financial performance of KPRI PLN Area IV in 2019 - 2020 by using the Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The elements selected from each ratio are Current Ratio, Quick Ratio, Equity Ratio to Total Debt, Assets to Debt Ratio, Equity Profitability Ratio, and Asset Profitability Ratio. This research was conducted at the Indonesian Civil Servant Cooperative (KPRI) PLN Area IV, Taman District, Sidoarjo Regency. The variable of this research is the financial performance of cooperatives as measured by a ratio analysis that has been determined based on the report on the Balance Sheet and Calculation of Business Results of KPRI PLN Area IV in 2019 – 2020. This study applies a quantitative research method with a descriptive approach. The results of this study indicate that the Financial Performance produced by the Employee Cooperative of the Republic of Indonesia PLN Area IV has a weakness, namely the occurrence of over-liquid due to excess current assets that are idle or not utilized properly. Meanwhile, short-term fund management has been going well. For this reason, there are several suggestions that must be considered by the KPRI PLN Area IV cooperative